The Role of Cystine/Glutamate Antiporter SLC7A11/xCT in the Pathophysiology of Cancer - Jyotsana, Nidhi; Ta, Kenny T.; DelGiorno, Kathleen E. (Frontiers in Oncology, 2022)
SLC7A11/xCT is an antiporter that mediates the uptake of extracellular cystine in exchange for glutamate. Cystine is reduced to cysteine, which is a rate-limiting precursor in glutathione synthesis; a process that protects cells from oxidative stress and is, therefore, critical to cell growth, proliferation, and metabolism. SLC7A11 is expressed in different tissues and plays diverse functional roles in the pathophysiology of various diseases, including cancer, by regulating the processes of redox homeostasis, metabolic flexibility/nutrient dependency, immune system function, and ferroptosis. SLC7A11 expression is associated with poor prognosis and drug resistance in cancer and, therefore, represents an important therapeutic target. In this review, we discuss the molecular functions of SLC7A11 in normal versus diseased tissues, with a special focus on how it regulates gastrointestinal cancers. Further, we summarize current therapeutic strategies targeting SLC7A11 as well as novel avenues for treatment.